IMPLEMENTASI TOTAL QUALITY MANAGEMENT BERBASIS CONTINUOUS IMPROVEMENT TERHADAP PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH - Indri Veviyanti Sugiarto; Izainiah; Anik Maiherawati; Ahmad Husin (STKIP Subang, 2026)
This study aims to examine and analyze in depth the implementation of Total Quality Management (TQM) based on Continuous Improvement in enhancing the quality of education in schools. This research employed a qualitative approach using a case study design. The study was conducted at SMP Negeri 1 Tapen Bondowoso from Maret 10 to May 10, 2026. Data were collected through in-depth interviews, participant observation, and document analysis. The data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing/verification. The findings reveal that the implementation of TQM based on continuous improvement at SMP Negeri 1 Tapen Bondowoso is established through the integration of five key components: visionary leadership, the implementation of the Plan–Do–Check–Act (PDCA) cycle, data-driven decision making, collaborative professional learning, and a quality culture oriented toward continuous improvement. The synergy among these components forms a systemic, adaptive, and evidence-based quality management system that enhances the effectiveness of school management, teachers' professionalism, the quality of teaching and learning processes, and institutional accountability. The novelty of this study lies in the formulation of an integrated TQM implementation model that positions visionary leadership, evidence-based decision making, collaborative professional learning, and the PDCA cycle as interconnected strategic pillars for achieving sustainable educational quality improvement.